Motivation for reckless criminal behavior (on the example of motor vehicle offenses) (Journal of actual problems of jurisprudence, 2019)
The priority tasks of the state should include the fight against imprudent delinquency because of the steady growth of processes caused by careless behavior of people. The interests of protecting the state and society from the harmful consequences of such behavior inevitably leads to an analysis of its motivation as the immediate and immediate personal determinant. Мotives are inherent in both intentional and careless crimes and in nature are motivations of socially dangerous behavior which led to harmful consequences. The concept of «motivation» is wider than the concept of «motive», which means a set of needs, interests, habits, etc., which can act as motives for unlawful behavior. The article emphasizes that the motive of careless behavior covers only the action, and its harmful consequences are unmotivated, which means that the connection between the motive and harmful consequences is noted. Suggested a classification of motives for careless criminal behaviors, indicated factors that motivating such behavior that should be taken into account in the development of preventive measures.